Introduction to Numerical Experiment on Plasma Focus using Lee Model Code - Gautam, P.; Khanal, R. (Himalayan Physics, 2015)
A dense plasma focus is table top machine producing short-lived very hot plasma and can cause nuclear fusion. Lee Model Code is a computer simulation package, which was successfully used in Mather and Fillipov type plasma focus. Lee Model couples the electrical circuit with the plasma focus dynamics, radiation and thermodynamics to simplify the complicated dynamics of plasma focus. This package enables us to simulate and analyze all of the gross properties. In this paper we present the importance of current fitting and the relation of it with other plasma focus parameter and overview of Lee Model Code together with physical basis, scope and the results obtained from the Lee Model Code. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page: 137-141